Pengaruh Pendapatan Asli Daerah, Dana Alokasi Umum, dan Dana Alokasi Khusus terhadap Belanja Daerah di Sulawesi Selatan - Muhammad Nur (Universitas Islam Negeri Alauddin Makassar, 2015)
This study aimed to analyze the influence of the Local Revenue (LR), General Allocation Fund (GAF) and Special Allocation Fund (SAF) to the Regional Shopping in 24 districts/cities in South Sulawesi province. Analysis method used is linear regression. The results showed LR and SAF partially significant effect on the Shopping Area. While GAF is not significant effect on regional expenditures.